2008
DOI: 10.1016/j.molcel.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Human Alu RNA Is a Modular Transacting Repressor of mRNA Transcription during Heat Shock

Abstract: Noncoding RNAs (ncRNAs) have recently been discovered to regulate mRNA transcription in trans, a role traditionally reserved for proteins. The breadth of ncRNAs as transacting transcriptional regulators and the diversity of signals to which they respond are only now becoming recognized. Here we show that human Alu RNA, transcribed from short interspersed elements (SINEs), is a transacting transcriptional repressor during the cellular heat shock response. Alu RNA blocks transcription by binding RNA polymerase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
401
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(415 citation statements)
references
References 41 publications
10
401
1
3
Order By: Relevance
“…TEs of a certain class might harbor not only TFBS, but also numerous other functional sequences in their consensus sequences, and, perhaps, mainly because these elements are defined by their designation, proposals with highly diverse functions are being published, even involving TEs with very narrow phylogenetic distributions Espinoza et al 2004Espinoza et al , 2007Lunyak et al 2007;Mariner et al 2008;Gong and Maquat 2011;Yakovchuk et al 2011;Carrieri et al 2012;Jady et al 2012;Holdt et al 2013;Ponicsan et al 2013;Wang et al 2013). Somatic LINE element integrations even have been implied in the development of the brain (Muotri et al 2005;Coufal et al 2009;Faulkner et al 2009;Singer et al 2010;Baillie et al 2011;Upton et al 2011;Perrat et al 2013;Reilly et al 2013).…”
Section: Te Functions: To the Moon!mentioning
confidence: 99%
“…TEs of a certain class might harbor not only TFBS, but also numerous other functional sequences in their consensus sequences, and, perhaps, mainly because these elements are defined by their designation, proposals with highly diverse functions are being published, even involving TEs with very narrow phylogenetic distributions Espinoza et al 2004Espinoza et al , 2007Lunyak et al 2007;Mariner et al 2008;Gong and Maquat 2011;Yakovchuk et al 2011;Carrieri et al 2012;Jady et al 2012;Holdt et al 2013;Ponicsan et al 2013;Wang et al 2013). Somatic LINE element integrations even have been implied in the development of the brain (Muotri et al 2005;Coufal et al 2009;Faulkner et al 2009;Singer et al 2010;Baillie et al 2011;Upton et al 2011;Perrat et al 2013;Reilly et al 2013).…”
Section: Te Functions: To the Moon!mentioning
confidence: 99%
“…Another example is the 3′ end of yeast lncRNA Srg1, which overlaps the promoter of the target gene Ser3 and inhibits Ser3 expression by occupying the binding site for transcription initiation factors in the Ser3 promoter [44]. At the transcriptional level, some lncRNAs inhibit the transcription of target genes by binding to the promoters of target genes and forming stable DNA-RNA triplex complexes [45], while others cooperate with transcription modulators in transcriptional regulation and interfere with the formation of the transcription initiation complex to repress transcription initiation and to rapidly alter gene expression patterns [46]. Post-transcriptionally, the formation of a RNA dimer via complementary base pairing between the lncRNA and the target mRNA can block the binding sites of transcription factors and processing-related factors, which regulate mRNA splicing, translation and degradation [47].…”
mentioning
confidence: 99%
“…1). In mammalian cells, heat activates the transcription of heat responsive genes, including HSPs, coincident with a bulk decrease in mRNA and protein syntheses, and this overall reprogramming of gene expression permits the selective synthesis of HSPs (40)(41)(42). In our previous studies using global-scale microarrays, we also detected a number of genes that were downregulated and participated in biological functions, including post-transcriptional modification and gene expression (43)(44)(45).…”
Section: Function Of Hsf1mentioning
confidence: 87%
“…This bulk decrease has been considered to represent a form of transcriptional suppression due to the binding of activated HSF1 to the promoter region of the gene (40). Mariner et al (41) recently reported that non-corded RNA is very closely related to the mechanism by which heat induces a decrease in gene expression.…”
Section: Function Of Hsf1mentioning
confidence: 99%